Agony of Choice – Trading off Stability and Competition in the Banking Markets - Falk Laser; Michael Hellwig (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We investigate the trade-off between financial stability and competition policy by focusing on the merger of ABN AMRO and Fortis Bank NL in the Dutch retail banking market. The financial crisis delayed the completion of the merger giving rise to anti-competitive behavior in the transitory period. Based on a structural model we simulate interest rates for savings accounts treating the banks as two separate entities despite a factually combined ownership. Our analysis builds on representative data on Dutch consumer choice for savings accounts conditional on individual choice sets and product characteristics covering the time period from 2008 to 2010. We model the demand for savings accounts as discrete choice for differentiated products using a random-coefficients logit model. On the supply side we assume Bertrand Nash competition in a multiproduct oligopoly. Our results indicate anti-competitive effects in terms of too low interest rates. To the best of our knowledge we are the first to apply merger simulation methods in the context of banking using disaggregated data.
Keywords: D22; G21; G34; L11; L25; L40; L41; 330; Antitrust; competition policy; merger analysis; state aid; retail banking; random-coefficients logit models; differentiated products.